1998
DOI: 10.1159/000014015
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk: Nutritional Aspects of a Dynamic Food

Abstract: The composition and volume of human milk progressively changes with the onset and duration of lactation and can be influenced by maternal nutritional factors. Current evidence indicates that infant demand is the major determinant of the quantity of milk transferred to the nursing infant. Human milk is remarkable for its variability, and ranges of intakes of milk constituents are comparable with normal patterns of infant growth and development. Lipids are by far the most variable constituents in human milk with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 33 publications
1
44
0
1
Order By: Relevance
“…It is well characterized that the nutritional and immunological composition of human milk changes over the lactation period (14) to meet the needs of the growing infant and contribute to the development of his/her host defense mechanisms, particularly in the gastrointestinal tract where the major load of new antigens is encountered. Our study is the first to reveal equal modification in the composition of breast milk microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…It is well characterized that the nutritional and immunological composition of human milk changes over the lactation period (14) to meet the needs of the growing infant and contribute to the development of his/her host defense mechanisms, particularly in the gastrointestinal tract where the major load of new antigens is encountered. Our study is the first to reveal equal modification in the composition of breast milk microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…During this period there is a largely direct relationship between food viscosity and caloric content since the viscosity and the caloric density of human breast milk appear to vary together. 23,24 Breast feeding may provide an important initial exposure to a general rule that thicker substances contain more calories than thinner substances. 24,25 This could mean that the difference in satiety responses between liquids and solids is based on learned behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Human milk is a dynamic body fluid that changes in nutritional and immunological composition during lactation (Haddad et al 2012) according to the time of day, type of milk and maternal ingestion of nutrients (Picciano 1998;França et al 2010França et al , 2012b and in disease (Roncada et al 2013). Moreover, the components of human milk and the pathophysiological processes of nursing mothers are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Diets high in sodium and low in potassium have been associated with hypertension (Sírio et al 2007). However, traces of minerals in human milk appear to be unaffected by maternal diet (Picciano et al 1998), and studies have shown that adequate ingestion of calcium during pregnancy prevents the adverse effects of gestational hypertension and lowers the risk of hypertension (Gillman et al 2004).…”
Section: Introductionmentioning
confidence: 99%